2003
DOI: 10.1002/cncr.11087
|View full text |Cite
|
Sign up to set email alerts
|

Protease‐activated receptor (PAR)‐1 and PAR‐2 participate in the cell growth of alveolar capillary endothelium in primary lung adenocarcinomas

Abstract: Conceptual design and experimental investigations are integrated for synthesizing diastereomeric salt crystallization processes for chiral resolution. An anti‐inflammatory drug ibuprofen and a common resolving agent N‐methyl‐D‐glucamine were chosen to illustrate this integrative approach. Bench data were generated in a systematic manner. Solvent screening was conducted first to identify the right solvent to precipitate the diastereomeric salts. Solid–liquid equilibrium data of the diastereomeric salt system we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 62 publications
(45 reference statements)
1
25
0
Order By: Relevance
“…PAR is a G-protein coupled receptor that is expressed in many cancer cells and cells in the microenvironment of a tumor. It can be activated by serine proteases like trypsin 74 and thrombin 75 by cleavage of its extracellular segment and transmit intracellular signals to stimulate cancer cell growth 76-78. A comprehensive review on hKs and its role in cancer with tabulated clinical implications are found in references 15 and 58, respectively.…”
Section: Target Proteasesmentioning
confidence: 99%
“…PAR is a G-protein coupled receptor that is expressed in many cancer cells and cells in the microenvironment of a tumor. It can be activated by serine proteases like trypsin 74 and thrombin 75 by cleavage of its extracellular segment and transmit intracellular signals to stimulate cancer cell growth 76-78. A comprehensive review on hKs and its role in cancer with tabulated clinical implications are found in references 15 and 58, respectively.…”
Section: Target Proteasesmentioning
confidence: 99%
“…This transactivation of the EGF-R by PAR2 agonists has never been reported before in any cell system. Whether this mechanism can be extended to other cancers such as gastric carcinoma (23), melanoma (24), lung carcinoma (25), pancreatic cancer (26), or glioblastoma (27) in which trypsin promotes cell proliferation remains to be established.…”
Section: Par2 Transactivates Egf-r In Colon Cancermentioning
confidence: 99%
“…TNF-α, triggered by the degranulation of MCs, induced ICAM-1 overexpression and facilitated the migration of neutrophils through the endogenously generated or exogenous chemokines KC/CXCL1 and LIX/CXCL5 [15]. MC tryptase was considered as one of the ligand enzymes for protease-activated receptor 2 (PAR-2) which was abundantly expressed in the airways [50]. Tryptase-mediated PAR-2 activation induced various lung disorders [51].…”
Section: Discussionmentioning
confidence: 99%